PTU-053 Is It Worth Repeating Previous Unremarkable Sb2 Capsules With The New Sb3?. (9th June 2014) - Dunn, S; Bevan, R; Neilson, L; Keay, R; Davison, C; Butt, F; Panter, S
Abstract : Introduction: Small bowel capsule endoscopy (SBCE) has become a valuable tool for investigating the small bowel and technology is rapidly advancing. One of the most recent devices available for capsule endoscopy (Pillcam® SB3, Given Imaging) has improved image resolution and a variable frame rate. The aim of this work is to address whether these innovations lead to increased mucosal visualisation and diagnostic yield in clinical practice and therefore whether a repeat SB3 capsule should be considered in those patients with an equivocal SB2 result. Methods: A review was undertaken of the last 100 Pillcam® SB2 capsules and the first 55 Pillcam® SB3 capsules to be performed at South Tyneside District Hospital (14/01/13–12/12/13). Visualisation of the ampulla was used as a surrogate marker of mucosal visualisation and diagnostic yield was assessed by reviewing the reports. Statistical significance was calculated using Fisher's exact test. Results: Results are summarised in Table 1 below. The ampulla was visualised in 14% of SB2 capsules and 18% of SB3 capsules (p > 0.05). 44% of SB2 capsules were abnormal and SB3 capsules were abnormal in 62% of cases (p < 0.05). Conclusion: It is recognised that the views obtained by SBCE can be compromised in the duodenum due to "rapid transit" and previous studies have suggested that due to this the ampulla of Vater is not often seen. 1 Variable frame rates aim to address this by capturing more images when the capsule is moving quicker. We showed no statistically significant difference between ampullary visualisation of the SB2 and SB3 capsules, although the trend was to a higher percentage visualisation with the SB3 capsule. The overall yield of pathology from SB3 capsules was significantly higher than that in SB2 capsules. Given the overall increased yield of pathology it may be beneficial to repeat an SB3 capsule in someone with a previously equivocal SB2 result. Reference: Koulaouzidis A, Rondonotti E, Karargyris A. Small-bowel capsule endoscopy: A ten-point contemporary review. World Journal of Gastroenterology 2013;19(24):3726–2840 Disclosure of Interest: S. Dunn Grant/research support from: Aquilant Endoscopy, R. Bevan Grant/research support from: Aquilant Endoscopy, L. Neilson: None Declared, R. Keay: None Declared, C. Davison: None Declared, F. Butt: None Declared, S. Panter: None Declared.